A Quantitative Model of Conflict Risk Degree at Non-Signalized Intersections. (2016) - Yin, Wei; Zou, Qingquan; Lv, Chenghao; Wu, Zhizhou; Tan, Guishan
Abstract: In order to investigate the relation of traffic conflicts and accidents, conflict risk degree is defined as the index of evaluating the impacts of traffic accidents on intersection safety, and a calculation model involving conflict probability, influencing degree and encountering time is developed as well. With survey data, the effectiveness and rationality of the conflict risk degree model were validated using VISSIM and SSAM. The results show that the maximum conflict risk degree is going straight-straight, and the number of conflicts is largest. Besides, risk degrees differ for different conflict types in spite of same conflict number. And conflict numbers are also different with same risk degrees.